Postnuptial Agreement as a Legal Instrument in Restoring the Validity of the Sale and Purchase Deed of Mixed Marriage Land - Ary Kareliana; Gusti Yosi Andri (Ann Publisher, 2026)
Background. The absence of a marriage agreement in a mixed marriage triggers a normative conflict between the Marriage Law and the Basic Agrarian Law (UUPA), which threatens the right of an Indonesian Citizen (WNI) over freehold title land (Hak Milik). Aims. This research aims to analyze the legal validity of the Land Deed of Sale and Purchase executed without a marriage agreement and to examine the legal certainty of a Postnuptial Agreement as a remedial instrument, based on Gustav Radbruch's theory. Methods. This doctrinal legal research employs statutory and conceptual approaches through a qualitative analysis of legal materials. Result. The results indicate that a freehold title AJB executed without a marriage agreement is legally defective and null and void due to violations of subjective and objective contract requirements, including the UUPA's prohibition on foreign ownership. This juridical defect is remedied through a Postnuptial Agreement pursuant to Constitutional Court Decision Number 69/PUU-XIII/2015, which serves as a curative and retroactive legal remedy. Conclusion. According to Gustav Radbruch's theory of legal certainty, this instrument confers actual legal certainty only if it is formalized in a Notarial Deed, registered with the civil registry agency (the principle of publicity), and free from any bad faith aimed at circumventing the law. Implementation. Furthermore, its retroactive effect must be strictly limited so as not to prejudice the rights of third parties and not to validate land objects that have exceeded the time limit for the relinquishment of rights.